Astaxanthin: A promising therapeutic agent for organ fibrosis. (February 2023) - Li, Ke; Wang, Wenhong; Xiao, Weihua
Abstract: Fibrosis is the end-stage pathological manifestation of many chronic diseases. Infiltration of inflammatory cells and activation of myofibroblasts are the most prominent features of fibrosis, with excessive deposition of extracellular matrix (ECM) in tissues leading to organ tissue damage, which eventually progresses to organ failure and leads to high mortality rates. At present, a large number of studies have been conducted on tissue fibrosis, and the pathological mechanism of fibrosis development has generally been recognized. However, the prevention and treatment of fibrosis is still an unsolved problem, and a shortage of drugs that can be used in the clinic persists. Astaxanthin (ASTX), a carotenoid, is widely known for its strong antioxidant capacity. ASTX also has other biological properties, such as anti-inflammatory, antiaging and anticancer properties. Recently, many papers have reported that ASTX inhibits the occurrence and development of fibrosis by regulating signaling molecular pathways, such as transforming growth factor-β/small mother against decapentaplegic protein (TGF-β1/Smad), sirtuin 1 (SIRT1), nuclear factor kappa-B (NF-κB), microRNA, nuclear factor-E2-related factor 2/antioxidant response element (Nrf 2/ARE) and reactive oxygen species (ROS) pathways. By targeting these molecular signaling pathways, ASTX may become a potential drug for the treatment of fibrotic diseases. In this review, we summarize the therapeutic effects of ASTX on organ fibrosis and its underlying mechanisms of action. By reviewing the results from in vitro and in vivo studies, we analyzed the therapeutic prospects of ASTX for various fibrotic diseases and provided insights into and strategies for exploring new drugs for the treatment of fibrosis. Graphical Abstract: ga1